2011
DOI: 10.1002/elps.201100323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of direct current dielectrophoresis on the trajectory of a non‐conducting colloidal sphere in a bent pore

Abstract: Dielectrophoresis has shown a wide range of applications in microfluidic devices. Force approximations utilizing the point-dipole method in dielectrophoresis have provided convenient predictions for particle motion by neglecting interactions between the particle and its surrounding electric and flow fields. The validity of this approach, however, is unclear when the particle size is comparable to the characteristic length of the channel and when the particle is in close proximity to the channel wall. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…When the particle enters the constriction where the electric field becomes highly nonuniform (Fig. B), the DEP force points toward the upper stream direction and tends to retard the motion of the incoming particle . However, since the Stokes force is two orders of magnitude higher than the DEP force, the particle still moves forward into the aperture with the carrying liquid.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…When the particle enters the constriction where the electric field becomes highly nonuniform (Fig. B), the DEP force points toward the upper stream direction and tends to retard the motion of the incoming particle . However, since the Stokes force is two orders of magnitude higher than the DEP force, the particle still moves forward into the aperture with the carrying liquid.…”
Section: Resultsmentioning
confidence: 88%
“…In order to describe pulse characteristics due to particle motion, electrical field, and flow field, all governing equations need to be coupled together during computation. Both particle and channel wall are assumed nonconducting and rigid .…”
Section: Methodsmentioning
confidence: 99%
“…(D) Equipotential contours plotted over the electric field strength around a particle moving through a bent cylindrical pore (left panel); The effect of initial position on particle trajectories where the solid lines represent the predictions from the boundary‐element method and the dashed lines represent the results from the point‐dipole method (right panel). Adapted with permission from House and Luo , © 2011 Wiley‐VCH.…”
Section: Curved Microchannelsmentioning
confidence: 99%
“…C). House and Luo applied a numerical approach based on the boundary‐element method to solve the coupled electric field, fluid flow, and particle motion in particle electrophoresis through a bent cylindrical pore. Their method can handle much closer particle–wall distances than the other numerical approaches such as the finite element method.…”
Section: Curved Microchannelsmentioning
confidence: 99%
“…3.44. However, it had been shown that this expression should not be used if the particle is of comparable size to the characteristic length of the electric field and can lead to an inaccurate prediction of the particle trajectories [121]. In this case the dielectrophoretic force F dep on a particle should be calculated with the surface integral over the Maxwell stress tensor T el [160]…”
Section: Non-zero Particle Size -Fem-ale Methods For DC Dielectrophoresismentioning
confidence: 99%